2004
DOI: 10.1093/ajcn/80.4.868
|View full text |Cite
|
Sign up to set email alerts
|

Method for estimating body weight in persons with lower-limb amputation and its implication for their nutritional assessment

Abstract: For persons with limb amputation, W(E) provides a better basis for appropriate nutritional evaluation than does W(O).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Arm span can be a reliable method used to measure height for disabled, old aged and deformed individuals (11,29) . A study by Yabanci et al (10) stated that MUAC and waist circumference were found to be moderately correlated with height, while previous work recommended the use of MUAC as a criterion standard that can be used to estimate height (30) . Others have argued that neither MUAC nor skinfold thickness has a good relationship ability with height (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Arm span can be a reliable method used to measure height for disabled, old aged and deformed individuals (11,29) . A study by Yabanci et al (10) stated that MUAC and waist circumference were found to be moderately correlated with height, while previous work recommended the use of MUAC as a criterion standard that can be used to estimate height (30) . Others have argued that neither MUAC nor skinfold thickness has a good relationship ability with height (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were previously healthy 18-50-year-old active duty male soldiers who sustained amputation of ≥3% estimated body weight loss (%EBWL) within 12 weeks of initial trauma. Extent %EBWL was determined by Osterkamp [24] and Mozumdar and Roy [25] estimations from dual-energy X-ray absorptiometry. Exclusion criteria included staged amputations; body mass index >35 kg/m 2 ; chronic kidney disease defined as eGFR <60 ml/min/1.73 m 2 , urine albumin-to-creatinine ratio >30 mg/g creatinine, or urine protein-to-creatinine ratio of >0.3 mg/mg creatinine; burns, chronic infection, malignancy, malnourishment, cardiovascular disease, cerebrovascular disease, lack of serum in the DoDSR; and AKI with any evidence of proteinuria defined as ≥1+ on urinalysis or urine protein-to-creatinine ratio of >0.3 mg/mg creatinine, obstruction, acute tubular necrosis, kidney trauma, or failure of SCr to return to <1.5 mg/dl within 72 h of volume resuscitation.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included prior renal or other transplantation and any major musculoskeletal deformity (e.g. amputation) that might compromise the validity of BMI Z-scores [29]. The study was approved by the CHOP Institutional Review Board and met criteria for waiver of consent.…”
Section: Study Subjectsmentioning
confidence: 99%